Farmers Perception and Agricultural Adaptation of Climate Change in Drought Prone Areas of Bangladesh (Journal of Environmental Science and Natural Resources, 2016)
The study was conducted at the selected areas of Bangladesh (Ishwardi and Lalpur upazila). It consisted of 80 randomly selected farmers through an interview schedule to identify the respondent's perception and their agricultural adaptation to climate change. The findings of the study indicate that the farmer?s perception about climate change was reasonable for the majority of farmers; majority of (47.5%) farmers claimed that annual precipitation was decreased, 57.5% farmers claimed that summer season temperature was increased, 48.75% farmers claimed that winter season temperature was decreased and 51.25% farmers claimed that yearly mean temperature was increased. However, 38.75% farmers said that the intensity of drought was increased and 58.75% farmers said that the intensity of hotness in summer season was increased. The finding of the study indicates that 70% of the farmers had medium agricultural adaptation capability compare to 23.75% farmers had low and 6.25% farmers had high agricultural adaptation capability. Education, farm size, annual income, credit received, cosmopoliteness had significant relationship with their agricultural adaptation to climate change.J. Environ. Sci. & Natural Resources, 9(1): 147-150 2016